UJI KINERJA PROTOTIPE ALAT PEMBERSIH GABAH - Yadi Sudirman; Sri Waluyo; Warji . (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Separation of paddy from empty grains and unexpected materials is one step in post harvest handlings done usually after cutting.  This step is acquired to have the high quality of paddy.  Separation that conventionally done by farmers, in general, is inefficient and can pose difficulties such us: high losses, high energy need, time consuming and depend on weather.  Application of separation machine is needed as an alternatif to overcome to those difficulties.  The purpose of this test is to determine the capacity and efficiency of work time required. The research was done in some steps: design of the equipment, manufacturing, testing and finally, data analysis.  The test was conducted in 3 levels of wind mover: 850 rpm, 1070 rpm and 1300 rpm.  Observation was focused on the percentage of empty grain, duration of separation and work capacity.  From the results, it can be concluded that the best wind mover for separation was 1070 rpm.  It could separate filled and empty grain effectively at 96,06%.  The average of work capacity of the equipment was 127,07 kg/hour.Keywords: Separation, rpm, Paddy.